Adoniram Judson Bound for Burma - Benge, Janet (Seattle YWAM, 2000)
As America's first foreign missionary, Adoniram Judson worked to translate the Bible into Burmese. He survived starvation, imprisonment, and torture both on land and at sea only to watch his family, coworkers, and friends succumb to death.
Keywords: Judson, Adoniram, -- 1788-1850 -- Juvenile literature. Bible. -- Judson. Judson, Adoniram, -- 1788-1850.